Family planning barriers in marginal contexts in Mexico City, Federal District: vision of the health care provider - Marcela Agudelo B (Universidad de Antioquia, 2009)
Objective: To approach the barriers to providing services of family planning in marginal areas of Iztapalapa and Tlalpan in the Federal District of Mexico City, from the perspective of health providers. Methodology: Qualitative exploration involved through focus groups with healthcare providers, both public and private, further topics such as socio-environmental, unmet needs in sexual and reproductive health (including family planning), relations gender, among others. Results:We found that among the main obstacles to access to family planning services are misinformation, culture and population beliefs, the inadequate training of health professionals in related areas, the shortage methods o f contraception, the deficiency infrastructure and resources. The barriers perceived by providers are coming from the people, and seldom alluded to the barriers arising from service of their own profession and/or personal convictions. Conclusion: Although the study focused on a specific social environment, this could reflect a reality in other contexts with similar characteristics, so this work constitutes a contribution to both practical and methodological analysis of the phenomenon.